The study of convex-dual-layer remote phosphor geometry in upgrading WLEDs color rendering index - Huu Phuc Dang; Nguyen Thi Phuong Loan; Nguyen Thi Kim Chung; Nguyen Doan Quoc Anh (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The white-light light-emitting diode (LED) is a semiconductor light source that usually has one chip and one phosphor layer. Because of that simple structure, the color rendering index (CRI) is really poor. Therefore, structure with double layer of phosphor and multiple chips has been studied with the phosphorus proportions and densities in the silicone are constantly changed to find the best option to improve optical properties. In research, we use red phosphor Ca5B2SiO10:Eu3+ layer to place above the yellow phosphor one, and both of them have a convex design. Then, the experiments and measurements are carried out to figure out the effects of this red phosphor as well as the convex-double-layer remote phosphor design on the LED’s performances. The measured results reveal that the light output is enhanced significantly when using convex-dual-layer structure instead of the single-layer design. Additionally, the Ca5B2SiO10:Eu3+ concentration benefits CRI and CQS at around 6600 K and 7700 K correlated color temperature (CCT). Yet, the lumen output shows a slight decline as this red phosphor concentration surpass 26% wt. Through the experiments, it is found that a double layer of chip and double phosphorus is the best structure which could support the quality of CRI and luminous flux.